Perhitungan Harga Pokok Produksi Pendekatan Full Costing Dan Variable Costing Untuk Menentukan Harga Jual Menggunakan Metode Cost Plus Pricing Pada Pengrajin Sepatu Bos Iwan - Amarulloh, Harry; Nuraini, Airin; Pradipto, Didit (LPPM Institut Bisnis dan Informatika Kesatuan, 2021)
To determine the selling price of a product, business owners must pay attention to the costs incurred in producing the product because costs are very important in determining the level of profit expected by the business owner. The calculation of the elements of production costs into the cost of goods manufactured is divided into 2 methods, namely the full costing method and the variable costing method. In doing business, there are still many MSMEs that have various obstacles, one of which is when calculating the cost of production and errors in setting the selling price. This research was conducted at MSME shoe craftsmen boss Iwan, this business is engaged in manufacturing, namely making shoes in Ciapus Village, Ciomas District, Bogor. The purpose of this study is (1) to find out how to calculate the cost of production according to MSME, (2) to find out how to calculate the cost of production using the full costing and variable costing methods, (3) to find out how the difference in calculation of the cost of production according to MSME with full costing and variable costing methods, (4) to find out how the difference in determining the selling price according to the company with the method of cost plus pricing. The analytical method used is comparative descriptive analysis. The results showed that the calculation of the cost of goods produced by SMEs boss Iwan shoe craftsmen is still simple and not detailed. In calculating the mainstay of the UMKM production only takes into account the cost of raw materials and direct labor costs only. In addition there are factory overhead costs in the form of auxiliary materials that are incorrectly calculated into the cost of raw materials. MSME boss Iwan also did not take into account variable factory overhead costs such as electricity, gas, engine and vehicle maintenance costs, and fixed factory overhead costs such as engine and vehicle depreciation costs. The suggestion for SME boss Iwan is that SME boss Iwan should use the full costing method in calculating the cost of production because this method takes into account all costs incurred during the production process so that the information produced becomes more accurate and the costs incurred reflect the true costs. In addition, it can help MSMEs in setting product selling prices and maximizing desired profits. Keywords: Cost of Production, Full Costing, Variable Costing, Cost Plus Pricing